CCNA 200-301 exam cram - Sequeira, Anthony (Exam cram (Pearson Education, Inc.), 2020)
Cisco CCNA 200-301 Exam Cram is the perfect study guide to help you pass the Cisco CCNA 200-301 exam, providing coverage and practice questions for every exam topic. The book contains an extensive set of preparation tools, including exam objectives, pre-assessments, topic overviews, Exam Alerts, Cram Savers, Cram Quizzes, chapter-ending practice questions, author notes and tips, and an expansive glossary. The book also contains the extremely useful Cram Sheet tear-out: a collection of essential facts and numbers in an easy-to-review format. Complementing all these great study tools is the powe.